Influence of Consumers’ Perceived Brand Innovativeness on Customer-Brand Identification and Brand Loyalty - Siti Nor Bayaah Binti Ahmad; Azizah Omar; Rudzi Munap; Roslan Mohd Rose (International Journal of Supply Chain Management, 2018)
In the current state of the business environment, an organisation considered innovativeness as one of the most valuable assets. The paradigm shift is to understand that innovation is viewed not only from the technological innovation but the innovative capability of the firm such as marketing, manufacturing process, or design innovativeness. This study focuses on consumer perceived brand innovativeness (CPBI) on brand identification and loyalty. Given rapid changes and the excess of new product availability, the influence on consumer loyalty might not be the same factors as found in the past studies. Therefore, the focus of this study is to examine the impact of predictors on loyalty behaviour. The current study develops a conceptual framework and reviews the literature on the role of brand innovativeness, brand identification and loyalty. Specifically, the focus is towards luxury cosmetic brands in Malaysia that were understudied. Hopefully, the study of brand innovativeness as an extrinsic information cue will assist marketers in understanding consumers better and enables an appropriate response to their needs.